Complete Genome Sequence of Streptococcus thermophilus KLDS 3.1003, A Strain with High Antimicrobial Potential against Foodborne and Vaginal Pathogens - Evivie, Smith E.; Li, Bailiang; Ding, Xiuyun; Meng, Yueyue; Yu, Shangfu; Du, Jincheng; Xu, Min; Li, Wan; Jin, Da; Huo, Guicheng; Liu, Fei (Frontiers in Microbiology, 2017)
Lactic acid bacteria play increasingly important roles in the food industry. Streptococcus thermophilus KLDS 3.1003 strain was isolated from traditional yoghurt in Inner Mongolia, China. It has shown high antimicrobial activity against selected foodborne and vaginal pathogens. In this study, we investigated and analyzed its complete genome sequence. The S. thermophilus KLDS 3.1003 genome comprise of a 1,899,956 bp chromosome with a G+C content of 38.92%, 1.995 genes and 6 rRNAs. With the exception of S. thermophilus M17TZA496, S. thermophilus KLDS 3.1003 has more tRNAs (amino acid coding genes) compared to some S. thermophilus strains available on the National Centre for Biotechnology Information database. MG-RAST annotation showed that this strain has 317 subsystems with most genes associated with amino acid and carbohydrate metabolism. This stain also has a unique EPS gene cluster containing 23 genes, and may be a mixed dairy starter culture. This information provides more insight into the molecular basis of its potentials for further applications in the dairy and allied industries.